Australian Government Policy in Facing the Post-Covid Workforce Crisis 2020-2022 - Maharani, Azzahra; Kurniawan, Sharla Martiza Putri; Hanabell, Stephanie Mathea; Choirunnisa, Feyza Nabila; Azmi, Muhammad Hilal (RMPI-BRIN, 2024)
COVID-19 has had an enormous impact on global markets and affected labor markets as there has been a drastic reduction in income and employment worldwide. The pandemic continues to pose pressing new legal issues for the Australian government, employers and workers. Governments are missing opportunities to address the gender pay gap. With the development of the COVID-19 pandemic, the Australian government is engaging in a wide range of activities and actions by Australian public service departments and agencies. The economic instability experienced by Australia during the COVID-19 pandemic has given impetus to the government's vision of economic recovery. Using qualitative methods, this research explains how the implementation of Australian government policies can work well. The conceptual framework used as a foundation is foreign policy according to K.J. Holsti and Rosenau. The results of the study will illustrate that the government policies implemented by Australia in dealing with the post-covid labor crisis in 2020-2022 can realize a significant reduction in unemployment.